Rapid synthesis of zeolites containing AFX structure and for selective NO X Reduced catalyst of at least one transition metal
By using AFX structured zeolite and transition metal catalyst based on fast synthesis in diesel engine exhaust gas, the problem of insufficient NOx conversion and N2O selectivity of existing catalysts at low temperatures is solved, and efficient NOx removal and good hydrothermal resistance is achieved. performance.
Patent Information
- Application Number
- CN202080029812.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-19
- Filing Date
- 2020-04-14
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-04-14
AI Technical Summary
The existing catalysts have insufficient performance in efficiently removing NOx from diesel engine exhaust gas, especially under low temperature conditions, and are not selective enough for nitric oxide N2O, making it difficult to meet increasingly stringent environmental standards.
Using a catalyst based on a fast synthesis AFX structured zeolite and at least one transition metal (especially copper), through a specific synthesis method, including mixing silicon oxide, aluminum oxide and organic nitrogen-containing compounds in an aqueous medium, to carry out water. Heat treatment and ion exchange are followed by heat treatment to form an efficient catalyst.
A lower NOx conversion reaction starting temperature and efficient NOx conversion rate over the entire operating temperature range are achieved, while maintaining good selectivity for N2O and having better resistance to hydrothermal aging.
Smart Images

Figure CN113710360B_ABST
Abstract
Description
Technical Field
[0001] The subject matter of the invention is a method for preparing a catalyst based on a zeolite of the AFX structure type obtained by rapid synthesis and on at least one transition metal, a catalyst prepared or preparable by this method, and a method for the selective catalytic reduction of NOx using said catalyst in the presence of a reducing agent, in particular in the case of internal combustion engines. Background Art
[0002] Nitrogen oxide (NOx) emissions from the combustion of fossil fuels have become a serious concern for society. Government authorities have set increasingly stringent standards to limit the impact of combustion emissions on the environment and health. For light-duty vehicles in Europe, according to the Euro 6c / Euro 6d-TEMP standard, NOx and particulate matter emissions must not exceed very low levels under all operating conditions. The new WLTC test cycle (Worldwide Harmonized Light Vehicles Test Cycle) and real driving emissions (RDE) regulations as well as compliance factors require the development of efficient pollution control systems to achieve these goals. Selective catalytic reduction (SCR) has become an effective technology for removing nitrogen oxides from oxygen-rich exhaust gases typical of diesel and spark-ignition engines in lean-mixture mode. Selective catalytic reduction is performed using a reducing agent, usually ammonia, and can therefore be referred to as NH3-SCR. The ammonia (NH3) involved in the SCR process is usually generated by decomposing an aqueous urea solution (AdBlue or DEF) and generates N2 and H2O when reacting with NOx.
[0003] Zeolites exchanged with transition metals are particularly used as catalysts in transportation for NH3-SCR applications. Small pore zeolites, especially copper-exchanged chabazite, are particularly suitable. They exist commercially in the form of silicoaluminophosphates Cu-SAPO-34 and aluminosilicates Cu-SSZ-13 (or Cu-SSZ-62). Their hydrothermal resistance and NOx conversion efficiency make them the current standard. However, as standards become more and more stringent, there is a need to further improve the performance of the catalysts.
[0004] The use of AFX structure-type zeolites for NH3-SCR applications is known, but few studies have evaluated the efficiency of catalysts using this zeolite.
[0005] Fickel et al. (Fickel, DW, & Lobo, RF (2009), The Journal of Physical Chemistry C, 114 (3), 1633-1640) have studied the use of copper-exchanged SSZ-16 (AFX structure type) for NOx removal. The zeolite was synthesized according to patent US 5,194,235, in which copper was introduced by exchange with copper (II) sulfate at 80°C for 1 hour. Recent results (Fickel, DW, D'Addio, E., Lauterbach, JA, and Lobo, RF (2011), 102 (3), 441-448) show excellent conversion and good hydrothermal resistance at a copper loading of 3.78 wt%.
[0006] The synthesis of AFX structured zeolites has been studied using various organic structural agents (Lobo, RF, Zones, SI, & Medrud, RC (1996), Chemistry of Materials, 8(10), 2409-2411) as well as synthesis optimization work (Hrabanek, P., Zikanova, A., Supinkova, T., Drahokoupil, J., Fila, V., Lhotka, M., Bernauer, B. (2016), Microporous and Mesoporous Materials, 228, 107-115).
[0007] Wang et al. (Wang, D. et al., Cryst Eng Comm., (2016), 18(6), 1000-1008) have studied the use of TEA-TMA mixtures to replace the structuring agent TMHD for the synthesis of silicoaluminophosphate SAPO-56 and obtained undesirable SAPO-34 and SAPO-20 phases. However, the incorporation of transition metals was not discussed.
[0008] Application US 2016 / 0137518 describes a quasi-pure AFX zeolite synthesized from silica and alumina sources in the presence of a structuring agent of the 1,3-bis(1-adamantyl)imidazolium hydroxide type, a catalyst for the preparation of an AFX zeolite exchanged with a transition metal, and its use for NH3-SCR applications. No specific form of the AFX zeolite is mentioned.
[0009] Recently, application US 2018 / 0093259 discloses the synthesis of small pore zeolites, such as AFX structured zeolites, from FAU-type zeolites in the presence of organic structuring agents such as 1,3-bis(1-adamantyl)imidazolium hydroxide and alkaline earth metal sources. It also discloses the application of the obtained AFX structured zeolite, in particular the use of the zeolite as a NOx reduction catalyst after exchange with a metal such as iron. At the same time, application US 2016 / 0096169A1 discloses the use of a catalyst based on a metal-exchanged AFX structured zeolite in NOx conversion, the zeolite having a Si / Al ratio of 15 to 50, and the AFX zeolite being obtained from a 1,3-bis(1-adamantyl)imidazolium hydroxide-type structuring agent. The results obtained in the NOx conversion specifically show that the selectivity of the catalyst prepared according to the applications US2018 / 0093259 and US 2016 / 0096169 for nitrous oxide does not exceed 20ppm.
[0010] Document JP 2014-148441 describes the synthesis of AFX zeolite-related solids, in particular the synthesis of copper-containing SAPO-56, which can be used for NO x Reduction. The synthesized solid is then added to a mixture containing an alcohol and a copper salt, and the whole mixture is calcined. Thus, after the formation of the solid SAPO-56 related to the AFX structural zeolite, the copper is added. The exchanged solid exhibits an increased resistance to the presence of water.
[0011] Ogura et al. (Bull. Chem. Soc. Jpn. 2018, 91, 355-361) demonstrated that copper-exchanged zeolites of the SSZ-16 type have very good activity compared to other zeolite structures even after hydrothermal aging.
[0012] WO 2017 / 080722 discloses the direct synthesis of copper-containing zeolites. The synthesis needs to start from FAU structure type zeolite and use TEPA complexing agent and M(OH) x Ingredients to obtain various types of zeolites, mainly CHA type zeolites. ANA, ABW, PHI and GME type zeolites are also produced.
[0013] The Applicant has found that catalysts based on zeolites of the AFX structural type prepared according to a specific rapid synthesis method and at least one transition metal, in particular copper, show advantageous performances in terms of NOx conversion and selectivity to N2O. In particular, the NOx conversion performance, in particular at low temperatures (T<250°C), is better than that obtained using catalysts of the prior art, such as catalysts based on copper-exchanged zeolites of the AFX structural type, while still maintaining a good selectivity to nitrogen monoxide N2O. Summary of the invention
[0014] The present invention relates to a method for preparing a catalyst, wherein the catalyst is based on a zeolite of the AFX structure type and at least one transition metal, and the method comprises at least the following steps:
[0015] i) mixing in an aqueous medium at least one source of at least one silicon oxide SiO2, at least one source of at least one aluminum oxide Al2O3, an organic nitrogen-containing compound R, at least one alkali metal and / or one alkaline earth metal M with a valence of n, n being an integer greater than or equal to 1, R, also known as a specific structuring agent, being 1,6-bis(methylpiperidinium)hexane dihydroxide, the reaction mixture having the following molar composition:
[0016] SiO2 / Al2O3 is 2.00 to 100, preferably 12 to 40,
[0017] H2O / SiO2 is 5 to 60, preferably 10 to 40,
[0018] R / SiO2 is 0.05 to 0.50, preferably 0.10 to 0.40,
[0019] M 2 / n O / SiO2 is 0.05 to 0.40, preferably 0.15 to 0.30,
[0020] wherein M is one or more alkali metals and / or alkaline earth metals selected from lithium, sodium, potassium, calcium, magnesium and mixtures of at least two of these metals, very preferably M is sodium, step i) is carried out for a time such that a homogeneous mixture known as a precursor gel is obtained;
[0021] ii) the precursor gel obtained at the end of step i) is subjected to a hydrothermal treatment at a temperature of 120° C. to 250° C., preferably 150° C. to 230° C., under autogenous pressure for 2 hours to 12 hours, preferably 2 hours to 10 hours, until the zeolite in the AFX structural type form is formed,
[0022] iii) at least one ion exchange consisting of contacting the solid obtained at the end of the previous step, under stirring at ambient temperature, for a period of 1 hour to 2 days, with a solution comprising at least one substance capable of releasing a transition metal, in particular copper, in reactive form in solution;
[0023] iv) thermal treatment, said thermal treatment advantageously comprising: drying the solid obtained in the previous step at a temperature of 20 to 150° C., preferably 60 to 100° C., for 2 to 24 hours, followed by at least one calcination in - optionally dry - air at a temperature of 450 to 700° C., preferably 500 to 600° C., for 2 to 20 hours, preferably 6 to 16 hours, more preferably 8 to 13 hours, the flow rate of the optionally dry air preferably being 0.5 to 1.5 L / h / g of solid to be treated, more preferably 0.7 to 1.2 L / h / g of solid to be treated.
[0024] At least one source of at least one silicon oxide SiO2 and / or at least one source of at least one aluminum oxide Al2O3 may be at least one FAU structural type zeolite having a SiO2 / Al2O3 molar ratio of 2.00 to 100.
[0025] Steps iii) and iv) can be reversed and / or optionally repeated.
[0026] Seed crystals of AFX structural type zeolite may be added to the reaction mixture of step i), preferably in an amount of 0.01% to 10% of the total mass of the sources of tetravalent (Si) and trivalent (Al) elements in the form of oxides (SiO2 and Al2O3) used in the reaction mixture, the seeds being not included in the total mass of the sources of tetravalent and trivalent elements.
[0027] Step i) may include the step of maturing the reaction mixture at a temperature of 20 to 80° C. for 30 minutes to 24 hours with or without stirring.
[0028] Advantageously, the ion exchange of step iii) is carried out by contacting the solid with a solution containing a single substance capable of releasing a transition metal, or by contacting the solid successively with different solutions, each of which contains at least one substance capable of releasing a transition metal, preferably a single substance capable of releasing a transition metal, the transition metals of the different solutions preferably being different from each other.
[0029] The at least one transition metal released in the exchange solution of step iii) can be selected from the group consisting of the following elements: Ti, V, Mn, Mo, Fe, Co, Cu, Cr, Zn, Nb, Ce, Zr, Rh, Pd, Pt, Au, W, Ag, preferably selected from the group consisting of the following elements: Fe, Cu, Nb, Ce or Mn, more preferably Fe or Cu, and more preferably the transition metal is Cu.
[0030] The content of transition metal introduced by ion exchange step iii) is advantageously between 0.5 and 6 mass%, preferably between 0.5 and 5 mass%, more preferably between 1 and 4 mass%, relative to the total mass of the anhydrous final catalyst.
[0031] The present invention also relates to a catalyst based on AFX zeolite and at least one transition metal, which can be obtained by the preparation method or directly obtained.
[0032] One or more transition metals can be selected from the group consisting of the following elements: Ti, V, Mn, Mo, Fe, Co, Cu, Cr, Zn, Nb, Ce, Zr, Rh, Pd, Pt, Au, W, Ag, preferably selected from the group consisting of the following elements: Fe, Cu, Nb, Ce or Mn, more preferably Fe or Cu, and more preferably the transition metal is Cu.
[0033] The total transition metal content is advantageously from 0.5 to 6 mass %, preferably from 0.5 to 5 mass %, more preferably from 1 to 4 mass %, relative to the total mass of the anhydrous final catalyst.
[0034] In one embodiment, the catalyst comprises only copper in an amount of 0.5 to 6% by weight, preferably 0.5 to 5% by weight, very preferably 1 to 4% by weight, relative to the total mass of the anhydrous final catalyst.
[0035] In another embodiment, the catalyst comprises a combination of copper and at least one other transition metal selected from the group consisting of Fe, Nb, Ce, and Mn, wherein the content of copper in the catalyst is 0.05% to 2% by mass, preferably 0.5% to 2% by mass, relative to the total mass of the anhydrous final catalyst, and the content of the at least one other transition metal is 1% to 4% by mass.
[0036] In another embodiment, the catalyst comprises a combination of iron and another metal selected from the group consisting of Cu, Nb, Ce, and Mn, with the iron content being 0.05 to 2 mass%, preferably 0.5 to 2 mass%, relative to the total mass of the anhydrous final catalyst, and the content of the other transition metal being 1 to 4 mass%.
[0037] The present invention also relates to a method for selectively reducing NOx by a reducing agent (such as NH3 or H2), which uses the above catalyst or a catalyst obtainable or directly obtainable by the preparation method.
[0038] The catalyst may be formed by depositing in the form of a coating on a honeycomb structure or a sheet structure.
[0039] The honeycomb structure may be formed of parallel channels open at both ends, or may comprise porous filter walls in which case adjacent parallel channels are alternately blocked at either side of the channel.
[0040] The amount of catalyst deposited on the structure is advantageously between 50 g / L and 180 g / L for a filtering structure, and between 80 g / L and 200 g / L for a structure with open channels.
[0041] The catalyst can be combined with a binder such as cerine, zirconia, alumina, non-zeolitic silica-alumina, titania, mixed oxides of the cerine-zirconia type, tungsten oxide and / or spinel so as to be formed by deposition in the form of a coating.
[0042] The coating can be used with a coating having adsorbed pollutants, especially NO x To reduce pollutants, especially NO x Or another coating combination that promotes the ability to oxidize contaminants.
[0043] The catalyst may be in the form of an extrudate comprising up to 100% of the catalyst.
[0044] The structure coated with the catalyst or obtained by extrusion of the catalyst can be integrated in the exhaust line of an internal combustion engine. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Shown is the chemical formula of the organic nitrogen-containing compound R, which is a structuring agent used in the synthesis method of the present invention.
[0046] Figure 2 X-ray diffraction patterns of the AFX structure-type copper-containing zeolites obtained according to Examples 2 to 5 are shown.
[0047] Figure 3 The relationship between the conversion rate C (in %) and the temperature T (in ° C.) obtained during the catalytic test of reducing nitrogen oxides (NOx) by ammonia (NH3) in the presence of oxygen (O2) under standard SCR conditions for the catalysts of Example 2 (CuAFX according to the present invention, the curve is represented by diamonds), the catalyst of Example 3 (CuAFX780 according to the present invention, the curve is represented by triangles), the catalyst of Example 4 (CuAFX720 according to the present invention, the curve is represented by squares), the catalyst of Example 5 (CuAFX600 according to the present invention, the curve is represented by circles) and the catalyst of Example 6 (comparative example, CuSSZ16, the curve is represented by crosses) is shown.
[0048] Further features and advantages of the synthesis method according to the invention, the catalyst according to the invention and the use according to the invention will become apparent on reading the following description of non-limiting exemplary embodiments with reference to the drawings described hereinafter. DETAILED DESCRIPTION
[0049] The present invention relates to a method for preparing a catalyst, wherein the catalyst comprises an AFX structure type zeolite and at least one transition metal, and the method comprises at least the following steps:
[0050] i) mixing in an aqueous medium at least one source of at least one silicon oxide SiO2, at least one source of at least one aluminum oxide Al2O3, or at least one FAU structure type zeolite having a SiO2 / Al2O3 molar ratio of 2.00 to 100, an organic nitrogen-containing compound R, at least one alkali metal and / or one alkaline earth metal M having a valence of n, n being an integer greater than or equal to 1, R, also known as a specific structuring agent, being 1,6-bis(methylpiperidinium)hexane dihydroxide, the reaction mixture having the following molar composition:
[0051] SiO2 / Al2O3 is 2 to 100, preferably 12 to 40,
[0052] H2O / SiO2 is 5 to 60, preferably 10 to 40,
[0053] R / SiO2 is 0.05 to 0.50, preferably 0.10 to 0.40,
[0054] M 2 / n O / SiO2 is 0.05 to 0.40, preferably 0.15 to 0.30,
[0055] wherein M is one or more alkali metals and / or alkaline earth metals selected from lithium, sodium, potassium, calcium, magnesium and mixtures of at least two of these metals, very preferably M is sodium, step i) is carried out for a time such that a homogeneous mixture known as a precursor gel is obtained;
[0056] ii) the precursor gel obtained at the end of step i) is subjected to a hydrothermal treatment at a temperature of 120° C. to 250° C., preferably 150° C. to 230° C., under autogenous pressure for 2 hours to 12 hours, preferably 2 hours to 10 hours, until the AFX structure-type zeolite is formed,
[0057] iii) at least one ion exchange consisting of contacting the solid obtained at the end of step ii) with a solution comprising at least one substance capable of releasing a transition metal, in particular copper, in reactive form in solution, for a period of 1 hour to 2 days, with stirring at ambient temperature;
[0058] iv) thermal treatment, said thermal treatment advantageously comprising: drying the solid obtained in the previous step at a temperature of 20 to 150° C., preferably 60 to 100° C., for 2 to 24 hours, followed by at least one calcination in - optionally dry - air at a temperature of 450 to 700° C., preferably 500 to 600° C., for 2 to 20 hours, preferably 6 to 16 hours, more preferably 8 to 13 hours, the flow rate of the optionally dry air preferably being 0.5 to 1.5 L / h / g of solid to be treated, preferably 0.7 to 1.2 L / h / g of solid to be treated.
[0059] Steps iii) and iv) can be reversed and / or optionally repeated.
[0060] The present invention also relates to a catalyst comprising an AFX structural type zeolite and at least one transition metal, which can be obtained by the above preparation method or directly obtained.
[0061] The invention finally relates to the use of the catalyst according to the invention in a process for the selective catalytic reduction of NOx in the presence of a reducing agent.
[0062] catalyst
[0063] The catalyst according to the invention comprises at least one AFX-type zeolite and at least one further transition metal, preferably copper.
[0064] According to the present invention, the one or more transition metals contained in the catalyst are selected from the group consisting of elements in Groups 3 to 12 of the Periodic Table (including lanthanide elements). In particular, the one or more transition metals contained in the catalyst are selected from the group consisting of the following elements: Ti, V, Mn, Mo, Fe, Co, Cu, Cr, Zn, Nb, Ce, Zr, Rh, Pd, Pt, Au, W, Ag.
[0065] Preferably, the catalyst according to the invention comprises copper, alone or in combination with at least one further transition metal selected from the abovementioned group of elements, in particular Fe, Nb, Ce, Mn.
[0066] Advantageously, the total transition metal content is from 0.5 to 6% by mass, preferably from 0.5 to 5% by mass, more preferably from 1 to 4% by mass, relative to the total mass of the finished catalyst in anhydrous form.
[0067] In the case where the catalyst contains only copper as transition metal, the transition metal content is advantageously from 0.5 to 6% by weight, preferably from 0.5 to 5% by weight, more preferably from 1 to 4% by weight, relative to the total mass of the anhydrous finished catalyst.
[0068] In the case where the catalyst contains copper and another element, the other element is, for example, preferably Fe, Nb, Ce, Mn, the copper content in the catalyst is 0.05% to 2% by mass, preferably 0.5% to 2% by mass, while the content of the other transition metal is preferably 1% to 4% by mass, the transition metal content being given as a mass percentage relative to the total mass of the final dry catalyst.
[0069] In the case where the catalyst contains only iron as transition metal, the iron content is between 0.5% and 4%, preferably between 1.5% and 3.5%, relative to the total mass of the anhydrous finished catalyst.
[0070] In the case where the catalyst contains iron and another element, the other element is, for example, preferably Cu, Nb, Ce, Mn, the iron content in the catalyst is 0.05% to 2% by mass, preferably 0.5% to 2% by mass, while the content of the other transition metal is preferably 1% to 4% by mass, the transition metal content being given as a mass percentage relative to the total mass of the final dry catalyst.
[0071] The catalyst according to the invention may also contain other elements, such as alkali metals and / or alkaline earth metals, for example sodium, originating in particular from the synthesis of the compounds of the reaction medium of step i) of the process for preparing the catalyst.
[0072] Method for preparing catalyst
[0073] Mixing step i)
[0074] This step is achieved by mixing at least one source of at least one silicon oxide SiO2, at least one source of at least one aluminum oxide Al2O3 and / or at least one FAU structure-type zeolite with a SiO2 / Al2O3 molar ratio of 2.00 to 100, an organic nitrogen-containing compound R (also called a specific structuring agent, 1,6-bis(methylpiperidinium)hexane dihydroxide), at least one alkali metal and / or one alkaline earth metal M with a valence of n, n being an integer greater than or equal to 1, in an aqueous medium, wherein the reaction mixture has the following molar composition:
[0075] SiO2 / Al2O3 is 2 to 100, preferably 12 to 40,
[0076] H2O / SiO2 is 5 to 60, preferably 10 to 40,
[0077] R / SiO2 is 0.05 to 0.50, preferably 0.10 to 0.40,
[0078] M 2 / n O / SiO2 is 0.05 to 0.40, preferably 0.15 to 0.30,
[0079] wherein M is one or more alkali metals and / or alkaline earth metals selected from lithium, sodium, potassium, calcium, magnesium and mixtures of at least two of these metals, very preferably M is sodium, and step i) is carried out for a time such that a homogeneous mixture known as precursor gel is obtained.
[0080] In the above molar compositions of the reaction mixtures and throughout the specification:
[0081] SiO2 represents the molar amount of tetravalent element silicon (Si) expressed in the form of oxide, and Al2O3 represents the molar amount of trivalent element aluminum (Al) expressed in the form of oxide,
[0082] H2O is the molar amount of water in the reaction mixture,
[0083] R is the molar amount of the organic nitrogen-containing compound,
[0084] M 2 / n O is provided by an alkali metal and / or alkaline earth metal source. 2 / n O is expressed as a molar amount of oxide.
[0085] According to the present invention, at least one source of oxide SiO2 is incorporated into the mixture for carrying out step (i) of the preparation method. The silicon source can be any of the sources commonly used for zeolite synthesis, such as powdered silica, silicic acid, colloidal silica, dissolved silica or tetraethoxysilane (TEOS). Among the powdered silica, precipitated silica can be used, especially those obtained by precipitation from solutions of alkali metal silicates, fumed silica (e.g. Cab-O-Sil) and silica gel. Colloidal silica with various particle sizes can be used, such as colloidal silica with an average equivalent diameter of 10 to 15 nm or 40 to 50 nm, such as those sold under registered trademarks such as Ludox. Preferably, the silicon source is Ludox HS-40. It is also possible to use at least one FAU structured zeolite with a SiO2 / Al2O3 molar ratio of 2.00 to 100 as an oxide SiO2 source alone or in a mixture with other SiO2 sources.
[0086] The aluminum source is preferably aluminum hydroxide or an aluminum salt (e.g., chloride, nitrate or sulfate), sodium aluminate, aluminum alcohol or aluminum oxide itself (preferably in hydrated or hydratable form, such as colloidal aluminum oxide, pseudoboehmite, gamma-alumina or alpha- or beta-alumina trihydrate). Mixtures of the above aluminum sources can also be used. At least one FAU structural type zeolite having a SiO2 / Al2O3 molar ratio of 2.00 to 100 can also be used as an oxide Al2O3 source, either alone or in a mixture with other Al2O3 sources.
[0087] According to the invention, at least one source of silicon dioxide and / or at least one source of aluminum can also be at least one FAU structural type zeolite having a SiO2 / Al2O3 molar ratio of 2.00 to 100.
[0088] According to the present invention, R is a nitrogen-containing organic compound, 1,6-bis(methylpiperidinium)hexane dihydroxide, which is incorporated into the reaction mixture to perform step (i) as an organic structuring agent.
[0089] According to the invention, at least one source of at least one alkali metal and / or alkaline earth metal M having a valence of n, n being an integer greater than or equal to 1, is used in the reaction mixture of step i), M being preferably selected from the group consisting of: lithium, potassium, sodium, magnesium and calcium and mixtures of at least two of these metals. Very preferably, M is sodium.
[0090] The source of at least one alkali metal and / or alkaline earth metal M is preferably sodium hydroxide.
[0091] It may be advantageous to add seeds of AFX structure-type zeolite to the reaction mixture during step i) of the method of the present invention to reduce the time required to form AFX structure-type zeolite crystals and / or the total crystallization time. The seeds also promote the formation of the AFX structure-type zeolite to the detriment of impurities. The seeds contain crystalline solids, in particular AFX structure-type zeolite crystals. The seeds are usually added in a proportion of 0.01% to 10% of the total mass of the tetravalent (silicon) and trivalent (aluminum) element sources in the form of oxides used in the reaction mixture, and the seeds are not included in the total mass of the tetravalent and trivalent element sources. When determining the composition of the reaction mixture and / or gel defined above, that is, when determining the various molar ratios of the reaction mixture composition, the seeds are not taken into account.
[0092] The mixing step i) is carried out until a homogeneous mixture is obtained, preferably for a time greater than or equal to 10 minutes, preferably with stirring at low or high shear rates by any system known to those skilled in the art.
[0093] At the end of step i), a homogeneous precursor gel is obtained.
[0094] Advantageously, during step i) of the process of the invention, the reaction mixture is aged and subsequently hydrothermally crystallized to control the crystal size of the AFX structural zeolite. The aged process also promotes the formation of the AFX structural zeolite to the detriment of impurities. During step i) of the process of the invention, the aged reaction mixture may be aged at ambient temperature or at a temperature of 20° C. to 80° C. with or without stirring for 30 minutes to 24 hours.
[0095] Hydrothermal treatment step ii)
[0096] According to step ii) of the process of the invention, the precursor gel obtained at the end of step i) is subjected to a hydrothermal treatment, preferably at a temperature ranging from 120 to 250° C. for 2 to 12 hours, until said AFX structural type zeolite (or “crystalline solid”) is formed.
[0097] Advantageously, the precursor gel is subjected to hydrothermal conditions, under autogenous reaction pressure, optionally with addition of gas (eg nitrogen), at a temperature preferably between 120° C. and 250° C., preferably between 150° C. and 230° C., until the AFX structural type zeolite has completely crystallized.
[0098] The time required to obtain crystallization is 2 to 12 hours, preferably 2 to 10 hours, and more preferably 2 to 8 hours.
[0099] The reaction is generally carried out with or without stirring, preferably with stirring. Stirring systems which can be used are any systems known to the person skilled in the art, for example inclined blades with counter-blades, stirring turbine mixers or endless screws.
[0100] Exchange step iii)
[0101] The process for preparing the catalyst according to the invention comprises at least one ion exchange step, which comprises contacting the crystalline solid obtained at the end of the previous step (i.e. the AFX zeolite obtained at the end of step ii) or, in the preferred case where steps iii) and iv) are reversed, the dried and calcined AFX zeolite obtained at the end of step iv) with at least one solution comprising at least one substance capable of releasing a transition metal, preferably copper, in a reactive form in the solution, the concentration of which depends on the amount of transition metal intended to be incorporated into the crystalline solid, under stirring at ambient temperature for a period ranging from 1 hour to 2 days, preferably from 6 hours to 12 hours.
[0102] It is also advantageous to obtain the AFX structural zeolite in protonated form after step ii). The protonated form can be obtained by ion exchange with an acid, in particular a strong inorganic acid such as hydrochloric acid, sulfuric acid or nitric acid, or with a compound such as ammonium chloride, sulfate or nitrate, before ion exchange with the transition metal.
[0103] The transition metal released in the exchange solution is selected from the group consisting of the following elements: Ti, V, Mn, Mo, Fe, Co, Cu, Cr, Zn, Nb, Ce, Zr, Rh, Pd, Pt, Au, W, Ag. Preferably, the transition metal is Fe, Cu, Nb, Ce or Mn, preferably Cu.
[0104] According to the present invention, "a substance capable of releasing a transition metal" is understood to mean a substance capable of dissociating in an aqueous medium, for example, a sulfate, nitrate, chloride, oxalate, or an organometallic complex of a transition metal, or a mixture thereof. Preferably, the substance capable of releasing a transition metal is a sulfate or nitrate of the transition metal.
[0105] According to the present invention, the solution contacted with the crystalline solid or the dried and calcined crystalline solid comprises at least one substance capable of releasing a transition metal, preferably a single substance capable of releasing a transition metal, preferably iron or copper, more preferably copper.
[0106] Advantageously, the process for preparing a catalyst according to the invention comprises an ion exchange in step iii) by contacting the crystalline solid with a solution containing a substance capable of releasing a transition metal, or by contacting the solid successively with a plurality of solutions each containing a substance capable of releasing a transition metal, each solution containing a different substance capable of releasing a transition metal.
[0107] At the end of the exchange, the solid obtained is advantageously filtered off, washed and then dried so as to obtain the catalyst in powder form.
[0108] The total amount of transition metal, preferably copper, contained in the final catalyst is between 0.5% and 6% by mass, relative to the total mass of the catalyst in anhydrous form.
[0109] According to one embodiment, the catalyst according to the invention is prepared by a process comprising an ion exchange step iii) such that the solid or the dried and calcined solid is brought into contact with a solution comprising a substance capable of releasing copper in solution in a reactive form. Advantageously, the total amount of copper contained in the final catalyst (i.e. at the end of the preparation process according to the invention) is between 0.5% and 6% by mass, preferably between 1% and 4% by mass, all percentages being by mass relative to the total mass of the final catalyst of the invention in anhydrous form obtained at the end of the preparation process.
[0110] Heat treatment step iv)
[0111] The preparation method according to the invention comprises a heat treatment step iv), which is carried out at the end of the previous step, i.e. at the end of the hydrothermal treatment step ii) or at the end of the ion exchange step iii), preferably at the end of the ion exchange step iii). Advantageously, steps iii) and iv) of the preparation method can be reversed. Steps iii) and iv) can each optionally be repeated.
[0112] Said step iv) of heat treatment comprises: drying the solid advantageously at a temperature of 20° C. to 150° C., preferably 60° C. to 100° C., for 2 to 24 hours, followed by at least one calcination in - optionally dry - air advantageously at a temperature of 450° C. to 700° C., preferably 500° C. to 600° C., for 2 to 20 hours, preferably 6 to 16 hours, more preferably 8 to 13 hours, the flow rate of the optionally dry air being preferably 0.5 to 1.5 L / h / g of solid to be treated, more preferably 0.7 to 1.2 L / h / g of solid to be treated. The temperature may be gradually increased before calcination.
[0113] The catalyst obtained at the end of the thermal treatment step iv) does not contain any organic substances, in particular no organic structuring agent R.
[0114] Specifically, the catalyst obtained by the method comprising at least the above steps i), ii), iii) and iv) has improved NO x Transformation properties.
[0115] Characterization of the catalyst prepared according to the invention
[0116] The catalyst comprises a zeolite of the AFX structure exchanged with at least one transition metal according to the International Zeolite Association (IZA) classification. The structure is characterized by X-ray diffraction (XRD).
[0117] X-ray diffraction (XRD) patterns were obtained by irradiating copper Kα1 Obtained by radiocrystallographic analysis. Based on the position of the diffraction peak represented by the angle 2θ, the Bragg relationship is used to calculate the lattice constant distance d of the sample hkl The Bragg relation is used to calculate d as a function of the absolute error Δ(2θ) assigned to the 2θ measurement. hkl The measurement error Δ(d hkl ). An absolute error Δ(2θ) equal to ±0.02° is usually accepted. The value assigned to d is measured based on the height of the corresponding diffraction peak. hkl The relative intensity of each value I rel Comparison of the diffraction pattern with the ICDD (International Center for Diffraction Data) database table using software such as DIFFRACT.SUITE also allows the identification of the crystalline phases present in the obtained material.
[0118] X-ray fluorescence (XRF) spectroscopy is used to qualitatively and quantitatively analyze the chemical substances present in the obtained materials. This is a technique that uses the physical properties of substances (X-ray fluorescence) for chemical analysis. The spectrum of X-rays emitted by the material is characteristic of the composition of the sample; by analyzing this spectrum, the elemental composition, i.e. the mass concentration of the elements, can be deduced from it.
[0119] The loss on ignition (LOI) of the catalyst obtained after the drying step (and before calcination) or after the calcination step of step iv) of the process according to the invention is generally between 5 and 18% by weight. The loss on ignition of a sample is denoted by the abbreviation LOI and corresponds to the difference in mass of the sample before and after a heat treatment at 1000° C. for 2 hours. It is expressed in %, corresponding to the mass loss in percentage. The loss on ignition generally corresponds to the loss of solvent contained in the solid, such as water, and also to the removal of organic compounds contained in the inorganic solid component.
[0120] Method for selectively reducing NOx by a reducing agent (such as NH3 or H2) using a catalyst according to the present invention
[0121] The invention also relates to the use of the catalyst of the invention which is directly prepared or can be prepared by the above-mentioned method for the selective reduction of NO by a reducing agent (such as NH3 or H2). x , advantageously in the form of a coating (or "washcoat") deposited on a honeycomb structure, primarily for mobile applications, or on a plate-like structure, in particular for stationary applications.
[0122] The honeycomb structure is formed of parallel channels open at both ends ("flow-through channels"), or comprises porous filtering walls, in which case adjacent parallel channels are alternately blocked at either side of the channel to force the gas flow through the walls ("wall-flow monolith"). The honeycomb structure thus coated constitutes a catalytic block. The structure may consist of cordierite, silicon carbide (SiC), aluminum titanate (AlTi), alpha-alumina, mullite, or any other material with a porosity of 30% to 70%. The structure may be formed in a metal plate, in a stainless steel containing chromium and aluminum (FeCrAl steel).
[0123] The amount of catalyst of the present invention deposited on the structure is from 50 g / L to 180 g / L for a filtering structure and from 80 g / L to 200 g / L for a structure with open channels.
[0124] The actual coating ("carrier coating") comprises the catalyst according to the invention, advantageously combined with a binder, such as cerine, zirconium oxide, alumina, non-zeolitic silica-alumina, titanium oxide, mixed oxides of the cerine-zirconia type, tungsten oxide, spinel. The coating is advantageously applied to the structure by a deposition method (known as washcoating), consisting in immersing the monolith in a suspension (or slurry) of the powdered catalyst according to the invention and optionally a binder, metal oxide, stabilizer or other promoter in a solvent (preferably water). This immersion step can be repeated until the desired amount of coating is obtained. In some cases, the slurry can also be sprayed onto the inside of the monolith. Once the coating has been deposited, the monolith is calcined at a temperature of 300° C. to 600° C. for 1 to 10 hours.
[0125] The structure may be coated with one or more layers. The coating containing the catalyst according to the invention is advantageously used with a substrate having adsorbed pollutants, in particular NO x To reduce pollutants, especially NO x Or another coating combination (ie, covering or being covered by another coating) that promotes the ability to oxidize pollutants (particularly ammonia).
[0126] Another possibility for the catalyst is in the form of extrudates. In this case, the structure obtained may contain up to 100% of the catalyst according to the invention.
[0127] The structure coated with the catalyst according to the invention is advantageously integrated in the exhaust line of an internal combustion engine which is mainly operated in lean mixture mode, that is to say with an excess of air relative to the stoichiometry of the combustion reaction, such as in the case of diesel engines. In the case of operation of these engines, the exhaust gas contains in particular the following pollutants: soot, unburned hydrocarbons (HC), carbon monoxide (CO), nitrogen oxides (NOx). An oxidation catalyst, whose function is to oxidize HC and CO, and a filter for removing soot from the exhaust gas can be placed upstream of the structure coated with the catalyst according to the invention, the function of the coated structure being to remove NOx, which operates in the range of 100° C. to 900° C., preferably 200° C. to 500° C.
[0128] Advantages of the invention
[0129] The catalyst of the invention, based on a zeolite of the AFX structure type obtained by rapid synthesis and at least one transition metal, in particular copper, has improved properties compared to the catalysts of the prior art. In particular, the use of the catalyst according to the invention makes it possible to obtain a lower NOx conversion reaction start temperature and an improved NOx conversion rate over the entire operating temperature range (150°C-600°C), while maintaining a good selectivity for N2O. It also has a better resistance to hydrothermal aging, ensuring high performance even after such aging.
[0130] Example
[0131] Example 1: Preparation of 1,6-bis(methylpiperidinium)hexane dihydroxide (structuring agent R)
[0132] 50 g of 1,6-dibromohexane (0.20 mol, 99%, Alfa Aesar) was placed in a 1 L round bottom flask containing 50 g of N-methylpiperidine (0.51 mol, 99%, Alfa Aesar) and 200 mL of ethanol. The reaction medium was stirred and refluxed for 5 hours. The mixture was then cooled to ambient temperature and then filtered. The mixture was poured into 300 mL of cold ether, the precipitate formed was then filtered out and washed with 100 mL of ether. The obtained solid was recrystallized in an ethanol / ether mixture. The obtained solid was dried under vacuum for 12 hours. 71 g of a white solid was obtained (i.e., 80% yield).
[0133] The product has the expected 1 H NMR spectrum. 1 H NMR (D2O, ppm / TMS): 1.27
[0134] (4H,m); 1.48(4H,m); 1.61(4H,m); 1.70(8H,m); 2.85(6H,s); 3.16(12H,m).
[0135] 18.9 g of Ag2O (0.08 mol, 99%, Aldrich) was placed in a 250 mL Teflon beaker containing 30 g of the prepared structuring agent 1,6-bis(methylpiperidinium)hexane dibromide (0.07 mol) and 100 mL of deionized water. The reaction medium was stirred for 12 hours in the absence of light. The mixture was then filtered. The filtrate obtained consisted of an aqueous solution of 1,6-bis(methylpiperidinium)hexane dihydroxide. The substance was analyzed by proton NMR using formic acid as a standard.
[0136] Example 2: Preparation of AFX structure-type zeolite containing 3% Cu according to the present invention
[0137] Preparation of AFX zeolite
[0138] 467.1 g of an aqueous solution of 1,6-bis(methylpiperidinium)hexane dihydroxide prepared according to Example 1 (18.36 wt%) are mixed with 4.3 g of deionized water. 19.72 g of sodium hydroxide (solid, 98 wt% purity, Aldrich) are added to the above mixture and the obtained preparation is kept under stirring for 10 minutes. Subsequently, 15.56 g of sodium aluminate (53.17% Al2O3, Strem Chemicals) are incorporated and the synthesis gel is kept under stirring for 15 minutes. Finally, 243.38 g of colloidal silica (Ludox HS40, 40 wt% SiO2, Grace) and 9.76 g of AFX zeolite seeds obtained by methods known to those skilled in the art are incorporated into the synthesis mixture under stirring. Without considering the AFX zeolite seeds, the molar composition of the mixture is as follows: 100SiO2: 5Al2O3: 16.7R: 22.4Na2O: 1836H2O, ie, a SiO2 / Al2O3 ratio of 20. The precursor gel is then transferred to an autoclave after homogenization. The autoclave is closed and then heated under autogenous pressure, the temperature increasing at 5°C / min to 150°C for 4 hours and stirring at 200 rpm using a system with four inclined paddles. The crystalline product obtained is filtered off, washed with deionized water and then dried at 100°C overnight. The loss on ignition is 14%. The solid is then introduced into a muffle furnace, where a calcination step is carried out: the calcination cycle consists of a temperature increase of 1.5°C / min to 200°C, a stabilization stage at 200°C for 2 hours, a temperature increase of 1°C / min to 550°C, followed by a stabilization stage at 550°C for 12 hours and then a return to ambient temperature.
[0139] The calcined solid product was analyzed by X-ray diffraction and identified as consisting of AFX structural type zeolite with a purity greater than 99.8% (ICDD file, PDF 04-011-1869). The SiO2 / Al2O3 molar ratio of the product was 10.2 as determined by XRF.
[0140] The calcined AFX zeolite was then contacted with a 3M NH4NO3 solution for 1 hour at 80°C with stirring. The ratio of the volume of the NH4NO3 solution to the mass of the solid was 10. The solid obtained was filtered off, washed, and then the exchange process was repeated 2 or more times under the same conditions. The final solid was separated, washed and dried at 100°C for 12 hours. XRD analysis showed that the product obtained was a pure AFX structural type zeolite.
[0141] The ammoniacal form of AFX zeolite was treated in an air stream at 550° C. for 8 hours with a temperature gradient of 1° C. / min. The product obtained was the protonated form of AFX zeolite.
[0142] Cu ion exchange
[0143] The protonated form of the calcined AFX zeolite was contacted with a [Cu(NH3)4](NO3)2 solution for 12 hours at ambient temperature with stirring. The final solid was isolated, washed and dried at 100°C for 12 hours.
[0144] The exchanged Cu-AFX solid obtained after contact with [Cu(NH3)4](NO3)2 solution was calcined at 550°C under air flow for 8 hours.
[0145] The calcined solid product was analyzed by X-ray diffraction and identified as AFX structural type zeolite (ICDD file, PDF 04-011-1869). The diffraction pattern produced by the solid was Figure 2 Available in.
[0146] The SiO2 / Al2O3 molar ratio of the product was 10.2, and the mass percentage of Cu was 3%, as determined by XRF.
[0147] The obtained catalyst was denoted as CuAFX.
[0148] Example 3: Preparation of AFX structure-type zeolite containing 3% Cu according to the present invention
[0149] Preparation of AFX zeolite
[0150] 29.3 g of an aqueous solution of 1,6-bis(methylpiperidinium)hexane dihydroxide prepared according to Example 1 (18.36% by weight) were mixed with 41.73 g of deionized water under stirring at ambient temperature. 0.764 g of sodium hydroxide (98% by weight, Aldrich) was dissolved in the above mixture under stirring at ambient temperature. Then, 0.675 g of amorphous aluminum hydroxide gel (amorphous Al(OH)3 gel, 58.55% by mass of Al2O3, Merck) was added to the synthesis mixture and it was kept under stirring for half an hour at ambient temperature. As soon as a homogeneous suspension was obtained, 7.56 g of FAU structural type zeolite (CBV780, SiO2 / Al2O3=98.22, Molecular Sieve International, LOI=8.52%) were added and the suspension obtained was kept under stirring for 30 minutes at ambient temperature. In order to promote the formation of AFX structure type zeolite, 0.614g of seed crystals of AFX structure type zeolite (10% relative to the mass of CBV780 zeolite) were added to the synthesis mixture and kept stirring for 5 minutes. The reaction mixture was then subjected to a step of aging for 24 hours with stirring (200rpm) at ambient temperature. The molar composition of the precursor gel was: 1SiO2: 0.05Al2O3: 0.167R: 0.093Na2O: 36.73H2O, that is, the SiO2 / Al2O3 ratio was 20. Subsequently, the precursor gel was transferred to a 160mL stainless steel reactor equipped with a stirring system with four inclined blades. The reactor was closed and then heated under autogenous pressure for 5 hours, the temperature was increased to 180°C at 5°C / min, and stirred at 200rpm to allow the AFX structure type zeolite to crystallize. The obtained crystalline product was filtered out, washed with deionized water, and then dried at 100°C overnight. The ignition loss of the dried solid was 14.69%.
[0151] The solid was then introduced into a muffle furnace where a calcination step was carried out: the calcination cycle consisted of a temperature increase of 1.5°C / min to 200°C, a stabilization phase at 200°C for 2 hours, a temperature increase of 1°C / min to 550°C, followed by a stabilization phase at 550°C for 12 hours, and then a return to ambient temperature.
[0152] The calcined solid product was analyzed by X-ray diffraction and identified as consisting of AFX structural type zeolite with a purity greater than 99 wt % (ICDD file, PDF 04-011-1869). The SiO2 / Al2O3 molar ratio of the product was 14.05 as determined by XRF.
[0153] The calcined AFX zeolite was then contacted with a 3M NH4NO3 solution for 1 hour at 80°C with stirring. The ratio of the volume of the NH4NO3 solution to the mass of the solid was 10. The solid obtained was filtered off, washed, and then the exchange process was repeated 2 or more times under the same conditions. The final solid was separated, washed and dried at 100°C for 12 hours. XRD analysis showed that the product obtained was a pure AFX structural type zeolite.
[0154] The ammoniacal form of AFX zeolite was treated in an air stream at 550° C. for 8 hours with a temperature gradient of 1° C. / min. The product obtained was the protonated form of AFX zeolite.
[0155] Cu ion exchange
[0156] The protonated form of the calcined AFX zeolite was contacted with a [Cu(NH3)4](NO3)2 solution for 12 hours at ambient temperature with stirring. The final solid was isolated, washed and dried at 100°C for 12 hours.
[0157] The exchanged Cu-AFX solid obtained after contact with [Cu(NH3)4](NO3)2 solution was calcined at 550°C under air flow for 8 hours.
[0158] The calcined solid product was analyzed by X-ray diffraction and identified as AFX structural type zeolite (ICDD file, PDF 04-011-1869). The diffraction pattern produced by the solid was Figure 2 Available in.
[0159] The SiO2 / Al2O3 molar ratio of the product was 14.05 and the mass percentage of Cu was 3% as determined by XRF.
[0160] The obtained catalyst was denoted as CuAFX780.
[0161] Example 4: Preparation of AFX structure-type zeolite containing 3% Cu according to the present invention
[0162] Preparation of AFX zeolite
[0163] 33.37 g of an aqueous solution of 1,6-bis(methylpiperidinium)hexane dihydroxide prepared according to Example 1 (18.36% by weight) are mixed with 37.15 g of deionized water under stirring at ambient temperature. 1.72 g of sodium hydroxide (98% by weight, Aldrich) are dissolved in the above mixture under stirring at ambient temperature. Once a homogeneous suspension is obtained, the addition of 7.79 g of FAU structural type zeolite (CBV720, SiO2 / Al2O3=33.52, Molecular Sieve International, LOI=6.63%) is started, and the obtained suspension is kept under stirring for 30 minutes at ambient temperature. In order to promote the formation of AFX structural type zeolite, 0.646 g of seeds of AFX structural type zeolite (10% by weight relative to the mass of CBV720 zeolite) are added to the synthesis mixture, which is kept under stirring for 5 minutes. The reaction mixture is then subjected to a step of maturation for 24 hours under stirring (200 rpm) at ambient temperature. The molar composition of the precursor gel is: 1SiO2: 0.0298Al2O3: 0.18R: 0.20Na2O: 34H2O, that is, the SiO2 / Al2O3 ratio is 33.55. Then, after homogenization, the precursor gel is transferred to a 160mL stainless steel reactor equipped with a stirring system with four inclined blades. The reactor is closed and then heated under autogenous pressure for 5 hours, the temperature is increased to 180°C at 5°C / min, and stirred at 200rpm to allow the AFX structure-type zeolite to crystallize. The obtained crystalline product is filtered out, washed with deionized water, and then dried at 100°C overnight. The ignition loss of the dried solid is 14.82%. The solid was then introduced into a muffle furnace where a calcination step was carried out: the calcination cycle consisted of a temperature increase of 1.5°C / min to 200°C, a stabilization phase at 200°C for 2 hours, a temperature increase of 1°C / min to 550°C, followed by a stabilization phase at 550°C for 12 hours, and then a return to ambient temperature.
[0164] The calcined solid product was analyzed by X-ray diffraction and identified as consisting of AFX structural type zeolite with a purity greater than 99 wt % (ICDD file, PDF 04-011-1869). The SiO2 / Al2O3 molar ratio of the product was 11.42 as determined by XRF.
[0165] The calcined AFX zeolite was then contacted with a 3M NH4NO3 solution for 1 hour at 80°C with stirring. The ratio of the volume of the NH4NO3 solution to the mass of the solid was 10. The solid obtained was filtered off, washed, and then the exchange process was repeated 2 or more times under the same conditions. The final solid was separated, washed and dried at 100°C for 12 hours. XRD analysis showed that the product obtained was a pure AFX structural type zeolite.
[0166] The ammoniacal form of AFX zeolite was treated in an air stream at 550° C. for 8 hours with a temperature gradient of 1° C. / min. The product obtained was the protonated form of AFX zeolite.
[0167] Cu ion exchange
[0168] The protonated form of the calcined AFX zeolite was contacted with a [Cu(NH3)4](NO3)2 solution for 12 hours at ambient temperature with stirring. The final solid was isolated, washed and dried at 100°C for 12 hours.
[0169] The exchanged Cu-AFX solid obtained after contact with [Cu(NH3)4](NO3)2 solution was calcined at 550°C under air flow for 8 hours.
[0170] The calcined solid product was analyzed by X-ray diffraction and identified as AFX structural type zeolite (ICDD file, PDF 04-011-1869). The diffraction pattern produced by the solid was Figure 2 Available in.
[0171] The SiO2 / Al2O3 molar ratio of the product was 11.42, and the mass percentage of Cu was 3%, as determined by XRF.
[0172] The obtained catalyst was denoted as CuAFX720.
[0173] Example 5: Preparation of AFX structure-type zeolite containing 3% Cu according to the present invention
[0174] Preparation of AFX zeolite
[0175] 28.35 g of an aqueous solution of 1,6-bis(methylpiperidinium)hexane dihydroxide prepared according to Example 1 (18.36% by weight) are mixed with 41.22 g of deionized water under stirring at ambient temperature. 1.26 g of sodium hydroxide (98% by weight, Aldrich) are dissolved in the above mixture under stirring at ambient temperature. 5.74 g of Aerosil 380 silica (100% by weight, Degussa) are subsequently poured in small portions under stirring. As soon as a homogeneous suspension is obtained, the addition of 3.43 g of a zeolite of the FAU structure type (CBV600, Molecular Sieve International, SiO2 / Al2O3=5.48, LOI=12.65%) is started, and the suspension obtained is kept under stirring at ambient temperature for 30 minutes. The reaction mixture is then subjected to a step of maturation under stirring (350 rpm) for 2 hours at ambient temperature. The precursor gel obtained has the following molar composition: 1SiO2: 0.05Al2O3: 0.125R: 0.12Na2O: 27.55H2O, i.e., the SiO2 / Al2O3 ratio is 20. 0.79 g of seeds of AFX structural zeolite (8.7% relative to the mass of anhydrous CBV600 zeolite and Aerosil 380 silica) are introduced into the precursor gel under stirring. Subsequently, the precursor gel containing the AFX zeolite seeds is transferred to a 160 mL stainless steel reactor equipped with a stirring system with four inclined blades. The reactor is closed and then heated under autogenous pressure for 7 hours, the temperature is increased to 190°C at 5°C / min, and stirred at 200 rpm to allow the AFX structural zeolite to crystallize. The obtained solid is filtered out, washed with deionized water, and then dried at 100°C overnight. The ignition loss of the dried solid is 12.6%.
[0176] The solid was then introduced into a muffle furnace where a calcination step was carried out: the calcination cycle consisted of a temperature increase of 1.5°C / min to 200°C, a stabilization phase at 200°C for 2 hours, a temperature increase of 1°C / min to 580°C, followed by a stabilization phase at 580°C for 10 hours, and then a return to ambient temperature.
[0177] The calcined solid product was analyzed by X-ray diffraction and identified as consisting of AFX structural type zeolite with a purity greater than 97 wt % (ICDD file, PDF 04-011-1869). The SiO2 / Al2O3 molar ratio of the product was 11.2 as determined by XRF.
[0178] The calcined AFX zeolite was then contacted with a 3M NH4NO3 solution for 1 hour at 80°C with stirring. The ratio of the volume of the NH4NO3 solution to the mass of the solid was 10. The solid obtained was filtered off, washed, and then the exchange process was repeated 2 or more times under the same conditions. The final solid was separated, washed and dried at 100°C for 12 hours. XRD analysis showed that the product obtained was a pure AFX structural type zeolite.
[0179] The ammoniacal form of AFX zeolite was treated in an air stream at 550° C. for 8 hours with a temperature gradient of 1° C. / min. The product obtained was the protonated form of AFX zeolite.
[0180] Cu ion exchange
[0181] The protonated form of the calcined AFX zeolite was contacted with a [Cu(NH3)4](NO3)2 solution for 12 hours at ambient temperature with stirring. The final solid was isolated, washed and dried at 100°C for 12 hours.
[0182] The exchanged Cu-AFX solid obtained after contact with [Cu(NH3)4](NO3)2 solution was calcined at 550°C under air flow for 8 hours.
[0183] The calcined solid product was analyzed by X-ray diffraction and identified as AFX structural type zeolite (ICDD file, PDF 04-011-1869). The diffraction pattern produced by the solid was Figure 2 Available in.
[0184] The SiO2 / Al2O3 molar ratio of the product was 11.2, and the mass percentage of Cu was 3%, as determined by XRF.
[0185] The obtained catalyst was denoted as CuAFX600.
[0186] Example 6
[0187] In this example, a Cu-exchanged SSZ-16 zeolite was synthesized according to the prior art. In this example, copper was introduced by ion exchange.
[0188] Preparation of SSZ-16 zeolite
[0189] 17.32 g of sodium hydroxide are dissolved in 582.30 g of deionized water under stirring (300 rpm) at ambient temperature. 197.10 g of sodium silicate are added to this solution and the whole mixture is homogenized by stirring (300 rpm) at ambient temperature. 9.95 g of CBV100 NaY zeolite are then added by stirring (300 rpm) and the addition is continued until the zeolite is dissolved. 43.67 g of structuring agent DABCO-C4 are dissolved in the solution obtained and then homogenized by stirring (450 rpm) at ambient temperature for 30 minutes.
[0190] The reaction mixture had the following molar composition: 100SiO2:1.67Al2O3:50Na2O:10DABCO-C4:4000H2O
[0191] The reaction mixture obtained in this mixing step was kept stirring at ambient temperature for 24 hours.
[0192] The gel obtained was introduced into a reactor and heated to 150° C. for 6 days with stirring (200 rpm). The crystals obtained were separated and washed with deionized water until a pH of the wash water of less than 8 was obtained. The washed crystalline solid was dried at 100° C. for 12 hours. The loss on ignition (LOI) was 18% by weight.
[0193] XRD analysis showed that the obtained product was a crude synthetic SSZ-16 zeolite of pure AFX structure type (ICDD file, PDF 04-011-1869).
[0194] The crude synthetic SSZ-16 zeolite was calcined at 550°C for 12 hours under a flow of dry air. The calcined SSZ-16 zeolite was contacted with a 3M NH4NO3 solution for 5 hours at ambient temperature with stirring. The ratio of the volume of the NH4NO3 solution to the mass of the solid was 10. The solid obtained was filtered off, washed, and the exchange process was repeated once more under the same conditions. The final solid was isolated, washed and dried at 100°C for 12 hours.
[0195] The ammonia form of SSZ-16 zeolite (NH4-SSZ-16) was treated in a dry air stream at 550°C for 8 hours with a temperature gradient of 1°C / min. The product obtained was the protonated form of SSZ-16 zeolite (H-SSZ-16).
[0196] Cu ion exchange on H-SSZ-16
[0197] H-SSZ-16 zeolite was contacted with a [Cu(NH3)4](NO3)2 solution for 12 hours at ambient temperature with stirring. The final solid was isolated, washed and dried, and calcined at 550°C under a stream of dry air for 8 hours. XRD analysis showed that the product obtained was a pure SSZ-16 zeolite of the AFX structure type (ICDD file, PDF 04-011-1869).
[0198] Chemical analysis by X-ray fluorescence (XRF) provided a SiO2 / Al2O3 molar ratio of 13 and a mass percentage of Cu of 3%.
[0199] The obtained catalyst was denoted as CuSSZ16.
[0200] Example 7: NO under standard SCR conditions x Conversion rate: Comparison of the catalyst according to the present invention with the prior art
[0201] The catalysts of Example 2 (CuAFX according to the present invention), Example 3 (CuAFX780 according to the present invention), Example 4 (CuAFX720 according to the present invention), Example 5 (CuAFX600 according to the present invention) and Example 6 (CuSSZ16 of the comparative example) were tested for catalytic reduction of nitrogen oxides (NOx) by ammonia (NH3) in the presence of oxygen (O2) under standard SCR conditions at different operating temperatures.
[0202] For each sample tested, 200 mg of the catalyst in powder form was placed in a quartz reactor. A representative feed of 145 L / h of an exhaust gas mixture from a diesel engine was added to the reactor.
[0203] The feed had the following molar composition: 400 ppm NO, 400 ppm NH3, 8.5% O2, 9% CO2, 10% H2O, the remainder being N2.
[0204] An FTIR analyzer is used to measure the concentrations of NO, NO2, NH3, N2O, CO, CO2, H2O, and O2 at the reactor outlet. The NOx conversion rate is calculated as follows:
[0205] Conversion rate = (NOx inlet – NOx outlet) / NOx inlet
[0206] The NOx conversion results under standard SCR conditions are as follows: Figure 3As shown, the curves CuAFX, CuAFX780, CuAFX720, CuAFX600 and CuSSZ16 correspond to tests performed using catalysts synthesized according to Example 2 (CuAFX, a catalyst according to the invention), Example 3 (CuAFX780, a catalyst according to the invention), Example 4 (CuAFX720, a catalyst according to the invention), Example 5 (CuAFX600, a catalyst according to the invention) and Example 6 (CuSSZ16, not a catalyst according to the invention). Obviously, the catalyst according to the invention can be used to convert NOx.
[0207] The catalysts CuAFX, CuAFX780, CuAFX720 and CuAFX600 synthesized according to the present invention show better performance in terms of NOx conversion rate over the entire test temperature range than the catalyst CuSSZ16 synthesized according to the prior art. The catalyst CuAFX780 according to the present invention reaches a maximum conversion rate of 100% at 259°C to 430°C, while the catalyst CuSSZ16 synthesized according to the prior art only reaches a conversion rate of 89% at 340°C to 400°C.
[0208] For standard SCR conditions, the catalyst initiation temperature is as follows:
[0209] Table 1
[0210] T50 T80 T90 T100 FX 180℃ 212℃ 228℃ 310℃ CuAFX780 159℃ 190℃ 204℃ 259℃ CuAFX720 173℃ 202℃ 217℃ 272℃ CuAFX600 172℃ 203℃ 222℃ 283℃ CuSSZ16 190℃ 257℃ 350℃ -
[0211] T50 corresponds to the temperature at which 50% of the NOx in the gas mixture is converted by the catalyst. T80 corresponds to the temperature at which 80% of the NOx in the gas mixture is converted by the catalyst. T90 corresponds to the temperature at which 90% of the NOx in the gas mixture is converted by the catalyst. T100 corresponds to the temperature at which 100% of the NOx in the gas mixture is converted by the catalyst.
[0212] Under standard SCR conditions, the catalysts CuAFX, CuAFX780, CuAFX720 and CuAFX600 synthesized according to the present invention have a performance in terms of initiation temperature and NOx conversion rate over the entire test temperature range that is far superior to the catalyst CuSSZ16 synthesized according to the prior art. Specifically, at the same conversion rate (50% or 80%), the initiation temperature (light-off temperature) obtained using the catalyst CuAFX according to the present invention is lower than the initiation temperature obtained using the catalyst CuSSZ16.
[0213] Example 8: NO in a fast SCR x Conversion rate: Comparison of the catalyst according to the present invention and the comparative catalyst
[0214] Catalysts synthesized according to the present invention (Examples 2, 3, 4 and 5) and sample CuSSZ16 synthesized according to the prior art (Example 6) were subjected to catalytic tests on the reduction of nitrogen oxides (NOx) by ammonia (NH3) in the presence of oxygen (O2) under fast SCR conditions at different operating temperatures.
[0215] 200 mg of the catalyst in powder form was placed in a quartz reactor. A representative feed of 218 l / h of an exhaust mixture from a diesel engine was added to the reactor. The feed had the following molar composition: 200 ppm NO, 200 ppm NO2, 400 ppm NH3, 8.5% O2, 9% CO2, 10% H2O, the remainder being N2 for fast SCR conditions.
[0216] An FTIR analyzer is used to measure the concentrations of NO, NO2, NH3, N2O, CO, CO2, H2O, and O2 at the reactor outlet. The NOx conversion rate is calculated as follows:
[0217] Conversion rate = (NOx inlet – NOx outlet) / NOx inlet
[0218] For fast SCR conditions, the catalyst initiation temperature is as follows:
[0219] Table 2
[0220] T50 T80 T90 T100 FX 178℃ 210℃ 235℃ 290℃ CuAFX780 162℃ 192℃ 215℃ 270℃ CuAFX720 161℃ 190℃ 214℃ 267℃ CuAFX600 166℃ 200℃ 220℃ 273℃ CuSSZ16 188℃ 233℃ 269℃ 402℃
[0221] T50 corresponds to the temperature at which 50% of the NOx in the gas mixture is converted by the catalyst. T80 corresponds to the temperature at which 80% of the NOx in the gas mixture is converted by the catalyst. T90 corresponds to the temperature at which 90% of the NOx in the gas mixture is converted by the catalyst. T100 corresponds to the temperature at which 100% of the NOx in the gas mixture is converted by the catalyst.
[0222] Under fast SCR conditions, the catalysts CuAFX, CuAFX780, CuAFX720 and CuAFX600 synthesized according to the present invention have better performance in terms of initiation temperature and NOx conversion rate over the entire test temperature range than the catalyst CuSSZ16 synthesized according to the prior art. Specifically, at the same conversion rate (50%, 80%, 90 or 100%), the initiation temperature obtained using the catalyst CuAFX according to the present invention is lower than the initiation temperature obtained using the catalyst Cu-SSZ-16.
[0223] Furthermore, for the catalyst CuAFX according to the invention, nitrogen oxide (N2O) emissions remain low (<20 ppm, 150° C. to 550° C.) over the entire tested temperature range.
Claims
1. A method for preparing a catalyst, wherein the catalyst is based on an AFX structure-type zeolite and at least one transition metal, the method comprising at least the following steps: i) mixing in an aqueous medium at least one source of at least one silicon oxide SiO2, at least one source of at least one aluminum oxide Al2O3, an organic nitrogen-containing compound R, at least one alkali metal and / or one alkaline earth metal M having a valence of n, n being an integer greater than or equal to 1, R, also known as a specific structuring agent, being 1,6-bis(methylpiperidinium)hexane dihydroxide, the reaction mixture having the following molar composition: SiO2 / Al2O3 is 2 to 100, H2O / SiO2 is 5 to 60, R / SiO2 is 0.05 to 0.50, M 2 / n O / SiO2 is 0.05 to 0.40, wherein M is one or more alkali metals and / or alkaline earth metals selected from lithium, sodium, potassium, calcium, magnesium and mixtures of at least two of these metals, step i) is carried out for a period of time such that a homogeneous mixture known as a precursor gel is obtained; ii) subjecting the precursor gel obtained at the end of step i) to a hydrothermal treatment at a temperature of 120° C. to 250° C. and under autogenous pressure for a period of 2 to 12 hours until the AFX structure-type zeolite is formed; iii) thermal treatment, the thermal treatment comprising: drying the solid obtained at the end of the previous step at a temperature of 20° C. to 150° C. for 2 to 24 hours, followed by at least one calcination in air at a temperature of 450° C. to 700° C. for 2 to 20 hours, the air flow rate being 0.5 to 1.5 L / h / g of the solid to be treated; iv) at least one ion exchange, which consists in contacting the solid obtained at the end of the previous step with a solution containing at least one substance capable of releasing a transition metal in reactive form in solution, the transition metal being copper Cu, and the content of the transition metal introduced by the ion exchange step iv) being between 0.5% and 6% by mass, for a period of 1 hour to 2 days, with stirring at ambient temperature.
2. The method for preparing a catalyst according to claim 1, wherein SiO2 / Al2O3 is 12 to 40.
3. The method for preparing a catalyst according to claim 1, wherein H2O / SiO2 is 10 to 40.
4. The method for preparing a catalyst according to claim 1, wherein R / SiO2 is 0.10 to 0.
40.
5. The method for preparing a catalyst according to claim 1, wherein M 2 / n O / SiO2 is 0.15 to 0.
30.
6. The method for preparing a catalyst according to claim 1, wherein M is sodium.
7. The method for preparing a catalyst according to claim 1, wherein The hydrothermal treatment of step ii) is performed at a temperature of 150°C to 230°C.
8. The method for preparing a catalyst according to claim 1, wherein The hydrothermal treatment in step ii) is performed for 2 to 10 hours.
9. The method for preparing a catalyst according to claim 1, wherein In the thermal treatment of step iii), the solid obtained at the end of the previous step is dried at a temperature ranging from 60°C to 100°C.
10. The method for preparing a catalyst according to claim 1, wherein: In the heat treatment of step iii), the at least one calcination is performed at a temperature of 500°C to 600°C.
11. The method for preparing a catalyst according to claim 1, wherein In the heat treatment of step iii), the at least one calcination is performed for 6 hours to 16 hours.
12. The method for preparing a catalyst according to claim 1, wherein: In the heat treatment of step iii), the at least one calcination is performed for 8 hours to 13 hours.
13. The method for preparing a catalyst according to claim 1, wherein: In the heat treatment of step iii), the flow rate of the air is 0.7 to 1.2 L / h / g of the solid to be treated.
14. The method for preparing a catalyst according to claim 1, wherein: At least one source of at least one silicon oxide SiO2 and / or at least one source of at least one aluminum oxide Al2O3 is at least one FAU structural type zeolite having a SiO2 / Al2O3 molar ratio of 2.00 to 100.
15. The method for preparing a catalyst according to any one of claims 1 to 14, wherein: The air is dry.
16. The method for preparing a catalyst according to any one of claims 1 to 14, wherein: Seed crystals of zeolite of the AFX structure type are added to the reaction mixture of step i).
17. The method for preparing a catalyst according to claim 16, wherein: The seeds are added in an amount of 0.01-10% of the total mass of the sources of tetravalent Si and trivalent Al elements in the form of their oxides SiO2 and Al2O3 used in the reaction mixture, which are not included in the total mass of the sources of tetravalent and trivalent elements.
18. The method for preparing a catalyst according to any one of claims 1 to 14, wherein: Step i) comprises the step of ripening the reaction mixture at a temperature of 20° C. to 80° C. for 30 minutes to 24 hours with or without stirring.
19. The method for preparing a catalyst according to any one of claims 1 to 14, wherein: The ion exchange of step iv) is performed by contacting the solid with a solution containing a single substance capable of releasing a transition metal, or by contacting the solid sequentially with different solutions, each of which contains at least one substance capable of releasing a transition metal.
20. The method for preparing a catalyst according to claim 19, wherein: The at least one substance capable of releasing a transition metal is a single substance capable of releasing a transition metal.
21. The method for preparing a catalyst according to claim 19, wherein: The transition metals of the different solutions are different from each other.
22. The method for preparing a catalyst according to any one of claims 1 to 14, wherein: The content of transition metal introduced by the ion exchange step iv) is between 0.5% and 5% by mass, relative to the total mass of the anhydrous final catalyst.
23. The method for preparing a catalyst according to any one of claims 1 to 14, wherein: The content of transition metal introduced by the ion exchange step iv) is between 1% and 4% by mass, relative to the total mass of the anhydrous final catalyst.
24. A catalyst based on AFX zeolite and at least one transition metal, directly obtainable by the process for preparing a catalyst according to any one of claims 1 to 23.
25. The catalyst according to claim 24, wherein The transition metal is Cu, and the total transition metal content is 0.5 mass % to 6 mass %.
26. The catalyst according to claim 24 or 25, wherein The total transition metal content is 0.5 to 5 mass % relative to the total mass of the anhydrous final catalyst.
27. The catalyst according to claim 24 or 25, wherein The total transition metal content is 1 to 4 mass % relative to the total mass of the anhydrous final catalyst.
28. The catalyst of claim 24 or 25, comprising only copper in an amount ranging from 0.5% to 6% by weight relative to the total mass of the anhydrous final catalyst.
29. The catalyst of claim 24 or 25, comprising only copper in an amount of 0.5 to 5% by weight relative to the total mass of the anhydrous final catalyst.
30. The catalyst of claim 24 or 25, comprising only copper in an amount of 1 to 4% by weight relative to the total mass of the anhydrous final catalyst.
31. A method for selectively reducing NOx by a reducing agent, wherein the reducing agent is NH3 or H2, using the catalyst according to any one of claims 24 to 30 or a catalyst directly obtained by the method for preparing a catalyst according to any one of claims 1 to 23.
32. The method for selectively reducing NOx according to claim 31, wherein: The catalyst is formed by being deposited in the form of a coating on a honeycomb structure or a sheet structure.
33. The method for selectively reducing NOx according to claim 32, wherein: The honeycomb structure is formed by parallel channels that are open at both ends, or comprises porous filtering walls in which case adjacent parallel channels are alternately blocked at either side of the channels.
34. The method for selectively reducing NOx according to claim 33, wherein: The amount of catalyst deposited on the structure is from 50 g / L to 180 g / L for a filtering structure and from 80 g / L to 200 g / L for a structure with open channels.
35. The method for selectively reducing NOx according to any one of claims 31 to 34, wherein: The catalyst is combined with a binder selected from ceria, zirconia, alumina, non-zeolitic silica-alumina, titania, ceria-zirconia type mixed oxides, tungsten oxide and / or spinel, so as to be formed by deposition in the form of a coating.
36. The method for selectively reducing NOx according to any one of claims 32 to 34, wherein: The coating is combined with another coating having the ability to adsorb pollutants to reduce the pollutants or promote the oxidation of pollutants, wherein the pollutants are NO x .
37. The method for selectively reducing NOx according to claim 31, wherein: The catalyst is in the form of an extrudate comprising up to 100% of the catalyst.
38. The method for selectively reducing NOx according to any one of claims 32 to 34, wherein: The structure coated with the catalyst or obtained by extrusion of the catalyst is integrated in the exhaust line of an internal combustion engine.
Citation Information
Patent Citations
AFX type silico-alumino-phosphate and method for producing the same as well as nitrogen oxide reduction method using the same
JP2014148441A
Molecular Sieve Catalyst For Treating Exhaust Gas
US20160096169A1
AFX zeolite
US20160137518A1
Novel zeolite synthesis with alkaline earth metal
US20180093259A1
Synthesis of SSZ-16 zeolite catalyst
US5194235A